Pengaruh Budaya Organisasi, Komunikasi Internal, dan Komitmen Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Mediasi Pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Lampung Selatan, Pesisir Barat, Tanggamus, dan Lampung Utara - Fakhrunnisa Fakhrunnisa; Ni Putu Widhia Rahayu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Optimal employee performance is a key determinant of public service effectiveness, yet the achievements of the Community and Village Empowerment Agency in several districts of Lampung Province remain low. This study aims to analyze the influence of organizational culture, internal communication, and commitment on employee performance, with job satisfaction as a mediator, in four priority districts. The research method employed was explanatory quantitative, utilizing a survey of 176 employees. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that job satisfaction has a dominant and significant influence on performance. Organizational culture and internal communication have a positive direct influence on both job satisfaction and performance. Commitment has a significant influence on job satisfaction but not a direct one on performance. Job satisfaction was proven to be a full mediator for the relationship between commitment and performance, and a partial mediator for the relationships of organizational culture and internal communication with performance. It is concluded that performance improvement requires a focus on enhancing job satisfaction through strengthening organizational culture, internal communication, and commitment. These findings provide practical implications for improving human resource management in local government agencies.